Adult Literacy Education for Conscientization: The Life and Legacy of Paulo Freire Revisited - Mlekwa, Victor M. (Papers in Education and Development, 2021)
Paulo Freire was one of the greatest educational thinkers and activists the world has ever seen. He wrote many unconventional books and articles and lectured in many countries about how education can and should make human beings unleash their potential to make what the world ought to be. The socio-economic context in which he was born and grew up shaped his thinking and motivated him to develop radical ideas on the aim, content and process of education in general, and adult education in particular, which thrust him in jail and exile. Many educational philosophers and practitioners have admired his intellectual sophistication but, unfortunately, not all of them have translated his revolutionary ideas into action. The political, socio-cultivating and technical problems particularly in developing societies have tended to constrain full application of his educational methodology. Keywords: adult literacy, conscientization, Paulo Freire